Comprehensive analysis of peptide-coding genes and initial characterization of an LRR-only microprotein in Marchantia polymorpha - Kobayashi, Haruaki; Murakami, Kazuaki; Sugano, Shigeo S.; Tamura, Kentaro; Oka, Yoshito; Matsushita, Tomonao; Shimada, Tomoo (Frontiers in Plant Science, 2023)
In the past two decades, many plant peptides have been found to play crucial roles in various biological events by mediating cell-to-cell communications. However, a large number of small open reading frames (sORFs) or short genes capable of encoding peptides remain uncharacterized. In this study, we examined several candidate genes for peptides conserved between two model plants: Arabidopsis thaliana and Marchantia polymorpha. We examined their expression pattern in M. polymorpha and subcellular localization using a transient assay with Nicotiana benthamiana. We found that one candidate, MpSGF10B, was expressed in meristems, gemma cups, and male reproductive organs called antheridiophores. MpSGF10B has an N-terminal signal peptide followed by two leucine-rich repeat (LRR) domains and was secreted to the extracellular region in N. benthamiana and M. polymorpha. Compared with the wild type, two independent Mpsgf10b mutants had a slightly increased number of antheridiophores. It was revealed in gene ontology enrichment analysis that MpSGF10B was significantly co-expressed with genes related to cell cycle and development. These results suggest that MpSGF10B may be involved in the reproductive development in M. polymorpha. Our research should shed light on the unknown role of LRR-only proteins in land plants.